INTEGRASI SISTEM INFORMASI PENDIDIKAN ISLAM DENGAN TEKNOLOGI DIGITAL - Lyindira Putri; Desyana Mustafa; Dina Hermina (PT. Hasba Edukasi Mandiri, 2026)
The integration of information systems with digital technology enables Islamic educational institutions such as madrasas, Islamic boarding schools (pesantren), and universities to improve governance effectiveness, enhance transparency of academic services, and enhance broader and more flexible access to learning. The method used was a literature review, exploring the latest research findings relevant to the digitalization of Islamic education. The study results indicate that the implementation of a Learning Management System, an academic information system, and educational big data contribute to improving the quality of management and learning based on Islamic values. However, obstacles remain in infrastructure, digital human resource literacy, data security, and concerns about the loss of spiritual touch in educational interactions. With targeted integration based on Islamic values, digital information systems have the potential to optimize the role of Islamic education in producing a superior and characterful generation in the digital era.Integrasi sistem informasi dengan teknologi digital memungkinkan lembaga pendidikan Islam seperti madrasah, pesantren, dan perguruan tinggi untuk meningkatkan efektivitas tata kelola, transparansi layanan akademik, serta akses pembelajaran secara lebih luas dan fleksibel. Metode yang digunakan adalah studi literatur melalui penelusuran hasil penelitian terkini yang relevan dengan digitalisasi pendidikan Islam. Hasil kajian menunjukkan bahwa penerapan Learning Management System, sistem informasi akademik, dan big data pendidikan berkontribusi pada peningkatan kualitas manajemen dan pembelajaran berbasis nilai Islam. Namun, hambatan masih ditemukan pada aspek infrastruktur, literasi digital SDM, keamanan data, serta kekhawatiran hilangnya sentuhan nilai spiritual dalam interaksi pendidikan. Dengan integrasi yang terarah dan berlandaskan nilai keislaman, sistem informasi digital berpotensi mengoptimalkan peran pendidikan Islam dalam mencetak generasi unggul dan berkarakter di era digital.